2017
DOI: 10.1038/npp.2017.216
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Hormones and Transdermal Nicotine Administration Independently and Synergistically Suppress Tobacco Withdrawal Symptoms and Smoking Reinstatement in the Human Laboratory

Abstract: Modeling intra-individual fluctuations in estradiol and progesterone may provide unique insight into the effects of ovarian hormones on the etiology and treatment of nicotine dependence. This randomized placebo-controlled laboratory study tested the independent and interactive effects of intra-individual ovarian hormone variation and nicotine on suppression of tobacco withdrawal symptoms and smoking behavior. Female smokers randomized to 21 mg nicotine (TNP; n=37) or placebo (PBO; n=43) transdermal patch follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…However, when data collected during the luteal phase were grouped based on progesterone levels, researchers found that women with high levels of progesterone reported significantly lower subjective effects. Similar findings show the effects of progesterone on reducing cravings 181,188,189,215 …”
Section: Resultssupporting
confidence: 84%
“…However, when data collected during the luteal phase were grouped based on progesterone levels, researchers found that women with high levels of progesterone reported significantly lower subjective effects. Similar findings show the effects of progesterone on reducing cravings 181,188,189,215 …”
Section: Resultssupporting
confidence: 84%
“…This indicates a possible inflection point in the progesterone curve when the rate of hormone increase begins to slow down, likely during increases in the luteal phase. These findings converge with our previous work showing that progesterone levels in combination with the magnitude and direction of change of progesterone may play an important role in smoking behavior 23 . Specifically, more rapid early luteal increases in progesterone appear to yield the greatest dampening effect on smoking and that this dampening effect diminishes as progesterone reaches asymptotic levels later in the luteal phase.…”
Section: Discussionsupporting
confidence: 90%
“…Hormone levels were centered at each participant's mean 33 (Person Mean Centered; PMC, where higher levels indicate that hormones are greater than the participant's average). Prior research suggests that the relationship between PMC hormone levels and smoking behavior may vary during the menstrual cycle leading to a nonlinear relationship and variation in the correlation between the two 21,23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a clinical report revealed that women have an easier time quitting smoking during the luteal phase, when E2 levels are decreasing and progesterone levels are relatively higher than E2 (Allen et al, 2008). During acute smoking abstinence, high levels of progesterone were associated with reduced negative affective states in nicotine-dependent women (Pang et al, 2018). Lastly, Nakajima et al (2019) found reduced cortisol responses to stressful stimuli in the luteal versus the follicular phase in a sample of nicotine-dependent women.…”
Section: Discussionmentioning
confidence: 99%